Acute Kidney Injury in Nephrotic Syndrome - Menon, Shina (Frontiers in Pediatrics, 2019)
Nephrotic syndrome (NS) is one of the commonest kidney diseases seen in childhood and is characterized by a relapsing remitting course. Various complications have been reported in children with NS, including infections, thromboembolism, hypovolemia and acute kidney injury (AKI). There is often a modest decrease in renal function in patients with active proteinuria due to decreased glomerular permeability that improves when they go into remission. However more pronounced AKI in NS is multifactorial in origin. It is most often secondary to hypovolemia, nephrotoxic medications and infections, although other reasons may also be seen. Recent years have seen an increase in the incidence of AKI in NS. There is limited data on the correlation between AKI in pediatric NS and long-term outcomes. A better understanding of this increasingly common condition will help improve patient outcomes.